Handbook of research on accounting and financial studies - Farinha, Luis M. Carmo, 1975-; Cruz, Ana Baltazar; Sebastião, João Renato (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book explores new trends in business, accounting, and financial studies"--Provided by publisher"--